Microbial Quality of Kupang Paste Products from Different Producers - Aliffia, Septin; Saidi, Ida Agustini (Indonesian Journal of Cultural and Community Development, 2024)
General Background the utilization of local ingredients, such as kupang, is integral to the culinary practices in Balongdowo Village, Sidoarjo Regency. Specific Background shrimp paste, a prominent product derived from kupang, is valued in the market, yet its quality raises concerns among consumers and producers. Knowledge Gap despite its economic significance, limited research has been conducted on the microbiological quality of kupang-based products, particularly during storage. Aims this study aims to evaluate the microbiological analysis of two kupang petis products from different producers in Balongdowo Village during ambient temperature storage. Results employing descriptive analysis across five storage treatments (P0: fresh, P1: 1 week, P2: 2 weeks, P3: 3 weeks, P4: 4 weeks), findings indicated that total plate count (TPC) in P0 treatment met national quality standards (SNI 2718.1: 2013), while yeast mold levels exceeded permissible limits. Notably, the TPC of sample B (1.6 x 10³) was lower than that of sample A (2.2 x 10³) in the fresh condition (P0). Novelty this research provides a comprehensive analysis of the microbiological quality of kupang petis, filling a significant gap in the literature. Implications the results underscore the necessity for rigorous quality control measures in the production and storage of shrimp paste to ensure consumer safety and compliance with health standards. Highlights: Microbiological quality assessment of kupang petis during storage. TPC values in fresh condition meet national standards. Yeast mold levels exceed permissible limits in stored samples. Keywords: Kupang, Shrimp Paste, Microbiological Analysis, Quality Standards, Storage